A biofeedback music-sonification system for gait retraining - Lorenzoni, V.; Maes, J. P.; Van den Berghe, P.; De Clercq, D.; de Bie, T.; Leman, M. (Proceedings of the 5th International Conference on Movement and Computing, 2018)
Auditory feedbacks are becoming increasingly popular in sports providing opportunities for monitoring and gait (re)training in ecological environments. We present the design process of a sonification strategy for modification of running parameters. The sonification provides real-time feedback of the performance through introduction of distortion of a baseline music track. The music BPM is continuously matched to the runners' cadence. The noise-based continuous feedback was able to significantly alter the mean running cadence in a non-instructed and non-disturbing way and performed better than standard verbal instructions. Although some of the participants did not respond effectively to the feedback, a large majority of the participants positively rated the feedback system in terms of pleasantness and motivation.